183k views
3 votes
Given: f(x) = x - 7 and h(x) = 2x + 3

Write the rule for h(f(x)).

2 Answers

4 votes

Answer: h(f(x)) = 2x - 11

Explanation:

User JeffE
by
5.2k points
6 votes

Answer:

h(f(x)) = 2x - 11

Explanation:

h(f(x)) is a "composite function." We use the function f(x) as the input to the function h(x):

h(x) = 2x + 3, or 2( x ) + 3; replacing x with f(x), or x - 7, we get:

h(f(x)) = 2(x - 7) + 3, or

h(f(x)) = 2x - 14 + 3, or

h(f(x)) = 2x - 11

User Imjosh
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.